Korelasi Masa Kerja dan Intensitas Nyeri terhadap Burnout Syndrome pada Perawat Kamar Operasi COVID-19 - Kukuh Widodo; Ah. Yusuf; Nuh Huda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the relationship between a work period and pain intensity with the incidence of burnout in COVID-19 operating room nurses. The method used is a descriptive correlation with a cross-sectional approach. The results of this research show that the p-value of years of service is 0.760 and r = 0.058; pain intensity obtained a value of p = 0.020 and r = 0.423. In conclusion, there is a relationship between pain intensity and the incidence of burnout; while the nurse's tenure is not related to burnout, but high pain intensity can cause burnout in nurses. Keywords: Burnout, Operating Room, Working Time, Pain, Nurse